Advances in group processes. Vol. 32 - Thye, Shane R.; Lawler, Edward J.; Emerald eBooks (Bingley, U.K. : Emerald, 2015)
Advances in group processes publishes theoretical analyses, reviews, and theory based empirical chapters on group phenomena. The series adopts a broad conception of "group processes." This includes work on groups ranging from the very small to the very large, and on classic and contemporary topics such as status, power, exchange, justice, influence, decision-making, intergroup relations and social networks. Previous contributors have included scholars from diverse fields including sociology, psychology, political science, philosophy, computer science, mathematics and organizational behavior.
Beyond three faces : toward an integrated social psychology of inequality / Jane D. McLeod, Tim Hallett, Kathryn J. Lively -- Sequence-network analysis : a new framework for studying action in groups / Benjamin Cornwell, Kate Watkins -- Expectation states, social influence, and affect control : opinion and sentiment change through social interaction / Kimberly B. Rogers -- How does status affect power use? New perspectives from social psychology / Ko Kuwabara -- Recruiting source effects : a social psychological analysis / Richard L. Moreland -- On identifying human capital : flawed knowledge leads to faulty judgments of expertise by individuals and groups / David Dunning -- Constructive leadership across groups : how leaders can combat prejudice and conflict between subgroups / Michael A. Hogg -- Collaboration among highly autonomous professionals : costs, benefits, and future research directions / Heidi K. Gardner, Melissa Valentine.
Keywords: Social Science -- Sociology -- General; Business & Economics -- Organizational Behavior; Social groups; Sociology -- Research; Psychology -- Research; Political science -- Research; Electronic books